High burden and frailty: association with poor cognitive performance in older caregivers living in rural areas - Brigola,Allan Gustavo (2017)
Abstract Introduction: Older caregivers living in rural areas may be exposed to three vulnerable conditions, i.e., those related to care, their own aging, and their residence context. Objective: To analyze the association of burden and frailty with cognition performance in older caregivers in rural communities. Method: In this cross-sectional survey, 85 older caregivers who cared for dependent elders were included in this study. Global cognition (Addenbrooke's Cognitive Examination – Revised; Mini Mental State Examination), burden (Zarit Burden Interview) and frailty (Fried's frailty phenotype) were assessed. All ethical principles were observed. Results: Older caregivers were mostly women (76.7%); mean age was 69 years. Cognitive impairment was present in 15.3%, severe burden in 8.2%, frailty in 9.4%, and pre-frailty in 52.9% of the older caregivers. More severely burdened or frail caregivers had worse cognitive performance than those who were not, respectively (ANOVA test). Caregivers presenting a high burden level and some frailty degree (pre-frail or frail) simultaneously were more likely to have a reduced global cognition performance. Conclusion: A significant number of older caregivers had low cognitive performance. Actions and resources to decrease burden and physical frailty may provide better cognition and well-being, leading to an improved quality of life and quality of the care provided by the caregivers.